2018
DOI: 10.1016/j.isci.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics in Two Extreme Neopterans Reveals General Trends in the Evolution of Modern Insects

Abstract: SummaryThe success of neopteran insects, with 1 million species described, is associated with developmental innovations such as holometaboly and the evolution from short to long germband embryogenesis. To unveil the mechanisms underlining these innovations, we compared gene expression during the ontogeny of two extreme neopterans, the cockroach Blattella germanica (polyneopteran, hemimetabolan, and short germband species) and the fly Drosophila melanogaster (endopterygote, holometabolan, and long germband spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 73 publications
11
79
1
Order By: Relevance
“…Therefore, we determined the Myo expression pattern in these 2 glands during the fourth, fifth, and sixth (final) instar female nymphs (N4, N5, and N6). In the CC-CA, the highest expression was observed in N5, in accordance with the pattern we found in our previous transcriptome analyses (10). Within N5, maximal expression was found at the beginning of the instar (N5D0) (;500 mRNA copies per 1000 copies of actin mRNA) and progressively decreased until it practically vanished at the end of the instar (N5D6).…”
Section: Morphologic Studies Of the Pgsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we determined the Myo expression pattern in these 2 glands during the fourth, fifth, and sixth (final) instar female nymphs (N4, N5, and N6). In the CC-CA, the highest expression was observed in N5, in accordance with the pattern we found in our previous transcriptome analyses (10). Within N5, maximal expression was found at the beginning of the instar (N5D0) (;500 mRNA copies per 1000 copies of actin mRNA) and progressively decreased until it practically vanished at the end of the instar (N5D6).…”
Section: Morphologic Studies Of the Pgsupporting
confidence: 90%
“…We presume, therefore, that the trigger role Myo plays in the premetamorphic stage of B. germanica may be extended to G. bimaculatus and perhaps to other hemimetabolan insects. Myo expression in D. melanogaster does not exhibit an especially prominent peak during the larval and pupa stages in the Northern blot analyses published by Lo and Frasch (11) or in the transcriptome profiles reported by us (10). The larva-pupa-adult transition in the holometabolan metamorphosis requires a relatively rapid pattern of decreasing-increasing-decreasing JH production (2,47).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These 210 embryos or unhatched nymphs showed a diversity of phenotypes that were classified into the following seven categories in different stages defined according to Tanaka [24]. Phenotype A ( [19]. In T. castaneum, the following five stages are represented: NFE and three sequential embryo stages: 8-16 h, 16-24 h, 24-48 h, which represent 30% development at 25°C [22], as well as 3-day-old embryo, late larva, pupa, and adult (female) [43].…”
Section: Depletion Of Bgzelda Results In Embryo Defectsmentioning
confidence: 99%
“…Studying transcriptomic differences along the ontogeny of D. melanogaster and the cockroach, Blattella germanica (a short germ-band and hemimetabolan species), we found that zelda showed a very different expression pattern in the two species [19]. In B. germanica, the expression was concentrated in early embryo, whereas in D. melanogaster zelda expression covered the entire embryogenesis [19]. We related this difference with the modes of metamorphosis of the studied species, hemimetabolan in B. germanica and holometabolan in D. melanogaster.…”
Section: Introductionmentioning
confidence: 98%